TINJAUAN KEJELASAN DAN KELENGKAPAN PENULISAN DIAGNOSIS DALAM KETEPATAN KODE POLI PENYAKIT DALAM DI RS MITRA MEDIKA BATANGHARI - Indra, Indra; Ilahi, Vitratul; Wisandra, Ade (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The accuracy of the diagnosis coder reflects the correspondence between the code assigned by the coding officer and the diagnosis in the patient's medical record according to ICD-10 and ICD-9. The problems found included 40% of the writing of diagnoses that was unclear and continuous, 20% of writing that was incomplete and used abbreviations, and 40% of diagnosis codes that were inaccurate. The aim of this research was to determine the clarity and completeness of writing in the accuracy of internal medicine poly diagnosis codes. at Mitra Medika Batanghari Hospital. This descriptive quantitative research was carried out at Mitra Medika Batanghari Hospital on 09-10 July 2022, with a population of 305 medical records of internal medicine patients and a sample of 75, taken using systematic random sampling. Data was collected through observation and checklist tables, and analyzed using univariate techniques. The research results obtained from 75 medical record files found that less than half, namely 27 (36.0%) wrote unclear diagnoses, more than half 61 (81.3%) wrote incomplete diagnoses, less than half 22 (29.3%) %) incorrect diagnosis code. Based on the research results, it can be concluded that there are still unclear and incomplete diagnoses written because they still use abbreviations and there are still incorrect diagnosis codes. It is recommended that the coder confirm again with the doctor concerned if there is an illegible diagnosis written so that there are no errors in assigning the diagnosis code.Keywords: Clarity, Completeness, Accuracy of Diagnosis Codes